Burden or Blessing? CEO Early-Life Adversity Experience and Firm Internationalization Performance - Zhou, Ping; Zhao, Yujie; Zhao, Kangsheng (Frontiers in Psychology, 2022)
Firm internationalization is a great challenge that needs a strong leader because of the uncertainty involved. Previous research has examined the antecedents of firm internationalization from the perspective of upper echelons theory, including CEO or TMT characteristics, yet little research has examined the role of CEO early-life adversity experiences. Based on the imprinting theory and upper echelons theory, this study explores the relationship between CEO early-life adversity experience and firm internationalization. Using data from Chinese listed companies during the period 2007-2017, we demonstrate that CEO early-life adversity experiences have a significantly positive effect on firm internationalization; the effect is stronger when the CEO with early-life adversity has a higher level of organization discretion and institutional discretion. The findings are robust to a battery of alternative variable definitions and estimation methods. We contribute to upper echelons theory and the research on internationalization antecedents by showing that CEO early-life adversity has a positive effect on firm internationalization. The findings suggest boards aspiring to expand internationally place weight on candidates’ early-life experiences while selecting and hiring CEOs and confer them managerial discretion to better play their strength after CEO’s appointment decision is made.